Hydropower Sustainability Assessment Protocol (HSAP) Implementation in Indonesia : A mini-review - Novi Andriany Teguh; Ainul Firdatun Nisaa (Journal of Infrastructure & Facility Asset Management, 2021)
Sustainability is one of the principles in infrastructure asset management. In a hydropower project, Hydropower Sustainability Tools (HST) are needed in assessing sustainability principles into practice when developing new hydropower projects. International Hydropower Association (IHA) published guidelines consist of three documents; one of them is Hydropower Sustainability Assessment Protocol (HSAP). This study is a mini-review focusing on the implementation of HSAP in hydropower projects in Indonesia, including the Pelosika project in Southeast Sulawesi, the Ir. H. Juanda project, and the Bendung Perjaya project in South Sumatra. HSAP has its advantages and disadvantages, it covers a variation of topics widely, but the assessment is somewhat subjective, time-consuming, and cost-intensive. HSAP is relatively new in Indonesia; there are not many publications regarding this topic. Future studies are recommended to know more about its potential in increasing the sustainability of hydropower projects.